Programming Clojure - Miller, Alex (Computer software developer); Halloway, Stuart Dabbs; Bedra, Aaron (Pragmatic programmers., 2018)
Getting started -- Exploring Clojure -- Unifying data with sequences -- Functional programming -- Specifications -- State and concurrency -- Protocols and datatypes -- Macros -- Multimethods -- Java Interop -- Building an application.